Conducting photopolymers on orthopeadic implants having a switch of priority between promoting osteogenic and antibacterial activity. Issue 3 (28th March 2018) - Liao, Jingwen; Chen, Weiguo; Yang, Mingjin; Zhou, Junli; Wang, Zhengao; Zhou, Yahong; Ning, Chengyun; Yuan, Hai
Abstract : Photopolymerized polymers with functional incorporation deliver a switch of priority between promoting osteogenic and antibacterial activity of implants. Abstract : For the long-term success of an implantation, an intelligent medium based on conducting photopolymers was decorated on implant surfaces, and a priority between promoting osteogenic and antibacterial activity could be dynamically switched through applying a specific electrical stimulus as needed at different clinical stages of implantation.